2016
DOI: 10.3847/0004-637x/819/2/148
|View full text |Cite|
|
Sign up to set email alerts
|

Unraveling the Complex Structure of Agn-Driven Outflows. I. Kinematics and Sizes

Abstract: Outflows driven by active galactic nuclei (AGNs) are often invoked as agents of the long-sought AGN feedback. Yet, characterizing and quantifying the impact on their host galaxies has been challenging. We present Gemini Multi-Object Spectrograph integral field unit data of six local (z 0.1 < ) and luminous (L 10In the first of a series of papers, we investigate the kinematics and constrain the size of the outflows. The ionized gas kinematics can be described as a superposition of a gravitational component tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
157
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(181 citation statements)
references
References 65 publications
22
157
2
Order By: Relevance
“…However, a reliable deblending and estimation of the contrast between resolved and unresolved emission is difficult for the obscured QSOs without a simultaneous characterization of the PSF. Thus, we are not able to directly verify that effect for obscured QSOs directly with the existing observations, but Villar-Martín et al (2016) and Karouzos et al (2016) have recently also reported very compact outflow sizes of <1−2 kpc after correction for a sample of luminous obscured QSOs at z < 0.6. While a consistent picture of the systematic effects is appearing, we cannot entirely rule out that the ionized gas properties on kpc scales are intrinsically different in obscured and unobscured AGN given the different selection criteria used for the obscured QSO samples.…”
Section: Given the Enhanced Asymmetry In The [O Iii] Light Distributionmentioning
confidence: 70%
See 3 more Smart Citations
“…However, a reliable deblending and estimation of the contrast between resolved and unresolved emission is difficult for the obscured QSOs without a simultaneous characterization of the PSF. Thus, we are not able to directly verify that effect for obscured QSOs directly with the existing observations, but Villar-Martín et al (2016) and Karouzos et al (2016) have recently also reported very compact outflow sizes of <1−2 kpc after correction for a sample of luminous obscured QSOs at z < 0.6. While a consistent picture of the systematic effects is appearing, we cannot entirely rule out that the ionized gas properties on kpc scales are intrinsically different in obscured and unobscured AGN given the different selection criteria used for the obscured QSO samples.…”
Section: Given the Enhanced Asymmetry In The [O Iii] Light Distributionmentioning
confidence: 70%
“…However, it remains unclear whether the observation of unobscured and obscured QSOs are equally affected. A direct study of beam-smearing effects for obscured QSOs is often infeasible but Villar-Martín et al (2016) and Karouzos et al (2016) have taken the beam smearing into account when analysing a sample of obscured QSOs and also report rather compact outflows size of 1-2 kpc. Given that we find [O iii] luminosity in obscured QSOs slightly enhanced compared to the AGN luminosity, the compact NLR region is not more obscured than in unobscured QSOs and makes the beam-smearing effect as important as for unobscured QSOs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high-ionization [O iii] λ5007 emission line has been frequently used to trace the ionized gas outflows in the narrow-line region (NLR), for investigating outflow properties using individual AGNs and a large sample (Boroson 2005;Greene & Ho 2005;Crenshaw et al 2010;Bae & Woo 2014;Harrison et al 2014;Liu et al 2014;Karouzos et al 2016;Woo et al 2016). For example, based on a sample of ∼400 quasars selected from the Sloan Digital Sky Survey (SDSS), Boroson (2005) suggested that both black hole mass and Eddington ratio play a role in determining the [O iii] kinematics.…”
Section: Introductionmentioning
confidence: 99%